Need strength, perceived need support, stress symptomatology, and performance in the context of oral exams: A typological approach - Schürmann, Linda; Kärner, Tobias; Ringeisen, Tobias (Frontiers in Psychology, 2022)
Based on self-determination theory, we investigated whether examinees are classifiable into profiles based on basic need strength and perceived need support that differ in stress parameters and achievement in the context of a standardized oral exam. 92 students reported their basic need strength before and perceived need support provided by the examiner once after the exam. Students indicated their emotions and stress perception at four measurement points, and we measured their saliva cortisol concurrently, analyzing stress-related changes over time. Latent profile analyses revealed two higher-quality (low/high, high/high) and two lower-quality (low/low, high/low) need strength/need support classes. Physio-affective stress development was typical of exam situations. Higher-quality classes that met or exceeded the needs displayed more beneficial stress and emotion response patterns than lower-quality classes. Gain-related emotions mediated achievement in the higher-quality classes. Need-supportive examiners can promote student well-being and achievement when they succeed in providing high need satisfaction.